2020
DOI: 10.1038/s41598-020-73167-0
|View full text |Cite
|
Sign up to set email alerts
|

Spatial–temporal dynamics and driving factor analysis of urban ecological land in Zhuhai city, China

Abstract: Ecological land is a type of land that has considerable ecological value. Understanding the evolution of urban ecological land in Zhuhai, China, holds great significance for revealing the evolution of ecological land in the Dawan District of southern China. We explored the temporal and spatial variation in urban ecological land in Zhuhai using the transformation matrix, equivalent ecological land, landscape index and ecological land center of gravity migration methods. Multivariate logistic regression was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 62 publications
1
25
1
Order By: Relevance
“…Global Moran’s I is a classic index for exploring spatial autocorrelation. It is mainly used to measure the spatial similarity of elements as a whole (Hu & Zhang, 2020). In this study, Moran’s I was used to describe the similarity of the level of equalization of public services in spatial distribution pattern, that is, spatial autocorrelation.…”
Section: Methodsmentioning
confidence: 99%
“…Global Moran’s I is a classic index for exploring spatial autocorrelation. It is mainly used to measure the spatial similarity of elements as a whole (Hu & Zhang, 2020). In this study, Moran’s I was used to describe the similarity of the level of equalization of public services in spatial distribution pattern, that is, spatial autocorrelation.…”
Section: Methodsmentioning
confidence: 99%
“…An in-depth consideration is to explore the interactions between tidal flats and two other land cover classes [8,9,17]. In this study, a total of six types of pixel-wise land cover conversions could be found by overlapping and comparing the maps of two years (Figure 3), and we only considered four of them which are directly related to tidal flats, including tidal flats to permanent water, tidal flats to lands, permanent water to tidal flats, and lands to tidal flats.…”
Section: Pixel Level Analysismentioning
confidence: 99%
“…Aside from the dynamic analyses on tidal flats, an in-depth consideration is to explore the spatiotemporal characteristics of the interactions between tidal flats and other land cover types. For example, a case study of Zhuhai City, China [17] assessed the gains and losses of tidal flats and other ecological lands between 1991 and 2018, during which the urban area had rapidly expanded. In addition, a model of ecological land change process was proposed with respect to multiple geographical factors, which was used to predict the land cover conversions in the future.…”
Section: Introductionmentioning
confidence: 99%
“…The possible modeling and quanti cation of the landscape through Geographic Information Systems and associated mathematical treatments offer unique opportunities to rigorously characterize, and therefore to guide the arrangement of landscapes towards sustainable city building and management (Hu and Zhang 2020). Within the two last decades, these approaches have been undergoing signi cant conceptual and methodological development, together with the implementation of new tools that permit quicker processing of increasingly massive datasets (Dumas et al 2008 (Turner et al 2001) provide numerical data describing the composition and physiognomy of landscapes and are well suited for even deeply modi ed environments such as the urban ones (Turner et al 2001;Rossi et al 2018).…”
Section: Introductionmentioning
confidence: 99%